How Microgravity Changes Galectin-3 in Thyroid Follicles. (11th September 2014) - Albi, Elisabetta; Curcio, Francesco; Lazzarini, Andrea; Floridi, Alessandro; Cataldi, Samuela; Lazzarini, Remo; Loreti, Elisabetta; Ferri, Ivana; Ambesi-Impiombato, Francesco Saverio
Abstract : After long-term exposure to real microgravity thyroid gland in vivo undergoes specific changes, follicles are made up of larger thyrocytes that produce more cAMP and express more thyrotropin-receptor, caveolin-1, and sphingomyelinase and sphingomyelin-synthase; parafollicular spaces lose C cells with consequent reduction of calcitonin production. Here we studied four immunohistochemical tumor markers (HBME-1, MIB-1, CK19, and Galectin-3) in thyroid of mice housed in the Mouse Drawer System and maintained for 90 days in the International Space Station. Results showed that MIB-1 proliferative index and CK19 are negative whereas HBME-1 and Galectin-3 are overexpressed. The positivity of Galectin-3 deserves attention not only for its expression but also and especially for its localization. Our results highlighted that, in microgravity conditions, Galectin-3 leaves thyrocytes and diffuses in colloid. It is possible that the gravity force contributes to the maintenance of the distribution of the molecules in both basal membrane side and apical membrane side and that the microgravity facilitates slippage of Galectin-3 in colloid probably due to membrane remodelling-microgravity induced.